Comparison of the Quality of DNA Template Isolation Results of the Resin Method with and Without Centrifugation: Perbandingan Kualitas DNA Template Hasil Isolasi Metode Resin dengan dan Tanpa Sentrifugasi - Jayanti, Liah Dwi; Mushlih, Miftahul (Universitas Muhammadiyah Sidoarjo, 2021)
The centrifugation process is able to separate the blood into several components, including the buffy coat. Buffy coat contains white blood cells that have a cell nucleus which is the source of DNA. This research uses descriptive experimental method. The samples used were 16 venous blood samples consisting of 8 samples without centrifugation (wholeblood) and 8 samples centrifuged (buffycoat). DNA isolation using the resin method. Quantitative analysis was performed using a UV-Vis spectrometer. The results showed that the average concentration and purity of DNA in the centrifuged sample was higher than in the sample without centrifugation. The result of this research is that the centrifuged sample (buffycoat) can be used for the DNA isolation process and has a higher purity and concentration value than the sample without centrifugation (wholeblood).